Estudio de prefactibilidad para la elaboración de cubos de concentrado de sabores peruanos mediante deshidratación osmótica - Azabache Correa, Daniel Alejandro (2022)
During the last few years and with greater incidence in times of COVID-19, public health has taken a great importance. There is a great interest of consumers to follow a healthy lifestyle; however, it is necessary that this does not consume to much time. To respond to this problem, the objective was to carry out a pre-feasibility study for the preparation of concentrated cubes of Peruvian flavors by osmotic dehydration. The work is divided into eight chapters, in the first chapter, the existing problem and the need to satisfy was determined and analyzed, which was a practical and nutritious product that could rescue the flavors of the national gastronomy. The objectives and hypotheses of the research were identified with the sources of information that support the work. The second chapter consists of the market study, the definition, and uses of the product; in addition, the target public and demand for the project were defined, the strategies for the introduction of the product in the market were established. The third chapter contains the determining factors for the location, which was in the district of Ate in Metropolitan Lima. In the fourth chapter, the optimum plant size was determined, defined by the size of the market. The fifth chapter defines the production process of the product, along with all the requirements and specifications to satisfy the demand. The sixth chapter consists of the human capital requirements of the company, which is sixty-three employees. The seventh chapter calculates the budgets necessary for both the start-up of the project and the five-year continuity of operations. Finally, the eighth chapter identifies the benefits and costs for the society due to the implementation of the project.